Cognitive deficits at age 22 years associated with prenatal exposure to methylmercury. (January 2016) - Debes, Frodi; Weihe, Pal; Grandjean, Philippe
Abstract: Prenatal exposure to mercury has been associated with adverse effects on child neurodevelopment. The present study aims to determine the extent to which methylmercury-associated cognitive deficits persist into adult age. In a Faroese birth cohort originally formed in 1986–1987 (N = 1, 022), prenatal methylmercury exposure was assessed in terms of the mercury concentration in cord blood and maternal hair. Clinical examinations of 847 cohort members at age 22 years were carried out in 2008–2009 using a panel of neuropsychological tests that reflected major functional domains. Subjects with neurological and psychiatric diagnoses were excluded from the data analysis, thus leaving 814 subjects. Multiple regression analysis included covariates previously identified for adjustment. Deficits in Boston Naming Test (BNT) and other tests of verbal performance were significantly associated with the cord-blood mercury concentration. Deficits were also present in all other tests applied, although most were not statistically significant. Structural equation models were developed to ascertain the possible differences in vulnerability of specific functional domains and the overall association with general intelligence. In models for individual domains, all of them showed negative associations, with crystallized intelligence being highly significant. A hierarchical model for general intelligence based on all domains again showed a highly significant negative association with the exposure, with an approximate deficit that corresponds to about 2.2 IQ points at a 10-fold increased prenatal methylmercury exposure. Thus, although the cognitive deficits observed were smaller than at examinations at younger ages, maternal diets with contaminated seafood were associated with adverse effects in this birth cohort at age 22 years. The deficits affected major domains of brain functions as well as general intelligence. Thus, prenatal exposure to this marine contaminant appears to cause permanent adverse effects on cognition.